La production d’un paysage par et pour le ski - Caterina Franco (Projets de Paysage)
This paper examines, through a historical perspective, the interrelations between the designing of new tourist resorts and the transformation of high mountain landscapes. Indeed, the creation of ski resorts is not only realised by the implantation of buildings and infrastructures at high altitudes. On the contrary, various components of the environment such as the forest, the morphology of the soil and the hydrography are modified. In addition, the biophysical and historical characteristics of the sites influence the design and construction processes of high-altitude resorts. We adopt as a perspective and a guide the professional career of the town planner and architect Laurent Chappis (1915-2013), thus allowing us to explore various case studies in the Franco-Italian Alps from the 1940s until the 1980s. We seek to understand the methods and tools used by the architect in defining resort plans and the elements that contribute to the construction of a landscape, and to comprehend how the architect's method and plans have evolved. By re-examining the past, we come to reflect on the relationship between project and environment in high mountain areas.